The concept of performative national identity: the theoretical methodological framework - M. R. Snegur (Вестник Майкопского государственного технологического университета)
Modern social and political changes emphasize the particular relevance of the problem of forming national identity in the context of often contradictory sociocultural processes. Leveling out negative social phenomena that exploit the category of national identity and developing its potential for the formation of civic values and harmonization of interethnic relations in Russian society necessitates a deep understanding of this phenomenon, which is considered primarily as a result of its construction by social institutions.   However, this process also takes the form of assimilation of elements of nation-building, passed through the filters of personal attitudes, representation of individual national identity in various social situations, which constitutes the problem of this research.   Based on the study of theoretical data, the author proposed a category of performative national identity based on the application of the approaches of social constructivism and symbolic interactionism. The methods of theoretical research were theoretical analysis and synthesis, induction and modeling. As a result, the category of performative national identity has been developed, which includes technologies, features, resources for construction and conscious and unconscious representation of national identity in everyday practices. The results of the research develop the theory and methodology of constructing national identity, expand the understanding of the process of formation of national identity as a result of the assimilation of collective memory through the prism of personal attitudes, and also allow us to study the features of the representation of national identity in various situations from the point of view of the dramaturgical approach.